2021
DOI: 10.1002/ece3.7852
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic selection for forage quality and quantity in response to phenology and insects in an Arctic ungulate

Abstract: Spatiotemporal variation in forage is a primary driver of ungulate behavior, yet little is known about the nutritional components they select, and how selection varies across the growing season with changes in forage quality and quantity. We addressed these uncertainties in barren‐ground caribou (Rangifer tarandus), which experience their most important foraging opportunities during the short Arctic summer. Recent declines in Arctic caribou populations have raised concerns about the influence of climate change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(39 citation statements)
references
References 109 publications
(237 reference statements)
0
33
1
Order By: Relevance
“…Rangifer tarandus in poor condition are less likely to survive and reproduce; recruitment to the population therefore diminishes with loss of body mass and body stores (Colman et al 2003, Kutz et al 2012, Witter et al 2012a, Raponi et al 2018). Harassment by flies affects foraging of female Rangifer tarandus and thus the annual productivity of herds in Alaska (Johnson et al 2018, 2021). The timing is particularly detrimental, as the end of fly season, and the resulting time of reduced body condition for Rangifer tarandus , is close to the start of winter (Mallory & Boyce 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Rangifer tarandus in poor condition are less likely to survive and reproduce; recruitment to the population therefore diminishes with loss of body mass and body stores (Colman et al 2003, Kutz et al 2012, Witter et al 2012a, Raponi et al 2018). Harassment by flies affects foraging of female Rangifer tarandus and thus the annual productivity of herds in Alaska (Johnson et al 2018, 2021). The timing is particularly detrimental, as the end of fly season, and the resulting time of reduced body condition for Rangifer tarandus , is close to the start of winter (Mallory & Boyce 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Past studies in the arctic have shown mosquitoes ( Culicidae ) alter forage selection and induce behavioral responses by caribou (e.g, grouping and movement; Johnson et al, 2021 ; Joly et al, 2020 ; Witter, Johnson, Croft, Gunn, & Gillingham, 2012 ; Witter, Johnson, Croft, Gunn, & Poirier, 2012 ). The avoidance behaviors we frequently observed (e.g., muzzle to the ground, head shaking, stomping and scratching), however, suggest harassment by oestrids ( Oestridae ) and tabanids ( Tabanidae ).…”
Section: Discussionmentioning
confidence: 99%
“…, our work shows that interior caribou face similar costs of insect harassment as coastal populations.Past studies in the arctic have shown mosquitoes (Culicidae) alter forage selection and induce behavioral responses by caribou (e.g, grouping and movement;Johnson et al, 2021;Joly et al, 2020;Witter, Johnson, Croft, Gunn, & Gillingham, 2012;F I G U R E 7The mean proportions of six forage functional types (lichen, shrub, graminoid, forb, Equisetum spp. and moss) estimated in the summer diets of caribou of the Fortymile Caribou Herd Alaska, USA and Yukon, Canada, 2011-2019.…”
mentioning
confidence: 99%
“…Arctic caribou exhibit the longest terrestrial migrations on earth to reach their summer ranges (Fancy et al, 1989;Joly et al, 2020b) which provide access to important forage resources (White et al, 1975;Griffith et al, 2002;Johnson et al, 2021). As capital breeders, caribou must maximize their foraging opportunities during the short Arctic summer to regain body stores lost during the previous winter and amass stores for the upcoming winter and reproductive cycle (Barboza and Parker, 2008;Parker et al, 2009;Taillon et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Arctic caribou subsist on lichen and senesced vascular vegetation most of the year (Russell et al, 1993;Joly et al, 2015), a diet that is generally high in digestible energy (DE) but very low in digestible protein [indexed by digestible nitrogen (DN)]. During the short Arctic summer growing season, recent studies have found that DE appears to be sufficient in caribou forage, while DN is only abundant in newly emergent vegetation, declining below maintenance levels after mid-summer (Barboza et al, 2018;Johnson et al, 2021). Given this constraint, Barboza et al (2018) hypothesized that caribou may be limited by their ability to store adequate protein when it is available, which could have effects on their subsequent reproductive success.…”
Section: Introductionmentioning
confidence: 99%